2008
DOI: 10.6026/97320630002260
|View full text |Cite
|
Sign up to set email alerts
|

A database on endemic plants at Tirumala hills in India

Abstract: Abstract:Medicinal plants play an important role in health care. The use of medicinal plants for treatment is growing in view of cost and non-compliance of modern medicine as in case of non-communicable diseases. Plants such as Boswellia, ovalifoliolata, Cycas beddomei, Pimpinella tirupatiensis, Pterocarpus santalinus, Shorea thumbuggaia, Syzygium alternifolium, Terminalia pallida are endemic to Tirumala hills of seshachalam range falling under the Eastern Ghats of India. These plants species have medicinal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…They include B. sacra, B. frereana, B. neglecta, B. microphylla, B. papyrifera, B. ogadensis, B. pirottae, B. rivae, B. madagascariensis, B. socotrana, B. popoviana, B. nana, B. ameero, B. bullata, B. dioscoridis, B. elongata, B. serrata and B. ovalifoliolata. Only the last two species have been reported to be distributed in India (Arabia 2005;Latheef et al 2008). Sunnichan et al (2005) mentioned that B. serrata is the only species found in India.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They include B. sacra, B. frereana, B. neglecta, B. microphylla, B. papyrifera, B. ogadensis, B. pirottae, B. rivae, B. madagascariensis, B. socotrana, B. popoviana, B. nana, B. ameero, B. bullata, B. dioscoridis, B. elongata, B. serrata and B. ovalifoliolata. Only the last two species have been reported to be distributed in India (Arabia 2005;Latheef et al 2008). Sunnichan et al (2005) mentioned that B. serrata is the only species found in India.…”
Section: Introductionmentioning
confidence: 99%
“…Our field surveys in the areas of Tirumala Hills have shown that the local tribes and others make deep incisions on the main trunk to extract the gum and resin, causing damage to trees which leads to population depletion. The gum is used to treat a number of conditions including ulcers, fever, stomach pain, scorpion sting, amoebic dysentery and hydrocele, while bark decoction is used for joint and rheumatic pains (Henry 2006;Latheef et al 2008). We have investigated the floral biology, breeding behaviour, pollination and foraging behavior of pollinators of B. ovalifoliolata in its natural area, and the observations and results obtained are discussed in the light of the existing relevant information.…”
Section: Introductionmentioning
confidence: 99%
“…belongs to the family papilionaceae/ fabaceae and popularly known as 'Red sander's (Naidu et al 2001). It was traditionally used in treatment for headache, skin diseases, fever, boils, scorpion-sting and to improve sight (Chopra et al 1956;Latheef et al, 2008). Previous chemical constituents revealed the presence of triterpenes, isoflavone, glucosids, savinin and calocedrin (Krishnaveni et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It mainly contains isoflavone glucosides and antitumor lignans like savinin and calocedrin 1 . Drinking of water twice a day in the cup of PS wood is in practice for treating diabetes 4,8,9 . Ethanol extract of stem-bark has been reported to have anti-hyperglycaemic activity 10 .…”
mentioning
confidence: 99%